Regional Capacity Building Training Workshop on Climate Basics and Climate Information for Agricultural Experts in Southern and Eastern Africa Regions - Ambaw, Gebermedihin; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change presents significant challenges to agriculture in Eastern and Southern Africa, a region heavily reliant on rainfed farming systems. To enhance resilience and productivity, agricultural experts need a strong foundation in climate systems and using Climate Information Services (CIS) effectively. A capacity-building training workshop aimed at equipping agricultural experts in Southern and Eastern Africa with the knowledge and skills to tackle climate change challenges effectively was held in Gaborone, Botswana, from September 16-20, 2024. The training workshop engaged a total of total of 57 participants from 18 countries, including 25% women.